Novel Ethanol‐Sensitive Mutants Identified in an F3 Forward Genetic Screen. (17th December 2019) - Swartz, Mary E.; Lovely, Charles Ben; McCarthy, Neil; Kuka, Tim; Eberhart, Johann K.
Abstract : Background: Fetal alcohol spectrum disorders (FASD) collectively refer to all deleterious outcomes due to prenatal alcohol exposures. Alterations to the face are common phenotypes in FASD. While alcohol exposure is the underlying cause of FASD, many variables modify the outcomes of such exposures. Genetic risk is one such variable, yet we still have a limited understanding of the nature of the genetic loci mediating susceptibility to FASD. Methods: We employed ENU‐based random mutagenesis in zebrafish to identify mutations that enhanced the teratogenicity of ethanol (EtOH). F3 embryos obtained from 126 inbred F2 families were exposed to 1% EtOH in the medium (approximately 41 mM tissue levels). Zebrafish stained with Alcian Blue and Alizarin Red were screened for qualitative alterations to the craniofacial skeleton between 4 and 7 days postfertilization (dpf). Results: In all, we recovered 6 EtOH‐sensitive mutants, 5 from the genetic screen itself and one as a background mutation in one of our wild‐type lines. Each mutant has a unique EtOH‐induced phenotype relative to the other mutant lines. All but 1 mutation appears to be recessive in nature, and only 1 mutant, au29, has apparent craniofacial defects in the absence of EtOH. To validate the genetic screen, we genetically mapped au29 and found that it carries a mutation in a previously uncharacterized gene, si:dkey‐88l16.3. Conclusions: The phenotypes of these EtOH‐sensitive mutants differ from those in previous characterizations of gene–EtOH interactions. Thus, each mutant is likely to provide novel insights into EtOH teratogenesis. Given that most of these mutants only have craniofacial defects in the presence of EtOH and our mapping of au29, it is also likely that many of the mutants will be previously uncharacterized. Collectively, our findings point to the importance of unbiased genetic screens in the identification, and eventual characterization, of risk alleles for FASD. Abstract : Genetics plays a role in risk and resilience to Fetal Alcohol Spectrum Disorder (FASD). However, our understanding of the genes involved in this risk is very limited. We used random mutagenesis to identify mutations that sensitize embryos to ethanol exposure. These mutants will provide important insight into the genetics of FASD. Ethanol exposure causes microcephaly and a reduction in the overall size of au32 mutants, compared to wild‐type controls.